Dentist Empathic Accuracy Is Associated With Patient-Reported Reassurance - Serge A. Steenen; Moniek A.J. Zeegers; Arjen J. van Wijk; Saif Al-Zubaidi; Minakshi Jethu-Ramkrishan; Aida Loddin; Jan de Lange; Ad de Jongh (Elsevier, 2023)
ABSTRACT: Objectives: The aim of this work was to determine dentists' ability to accurately estimate patients' anxiety level during dental treatment (ie, "empathic accuracy") and to determine the strength of the association between empathic accuracy and patient-reported reassurance. Methods: A cross-sectional study was conducted amongst 177 adult patients who underwent different invasive dental procedures (ie, extractions or procedures requiring injections and drilling) performed by 10 different dentists from 3 dental offices in the Netherlands. Patients reported their anxiety level during treatment and the extent to which they felt reassured by the dentist using a visual analogue scale (VAS). Simultaneously, the dentists estimated patients' anxiety level. Empathic accuracy was calculated as an absolute difference between patient-reported anxiety (100-point VAS) and dentist estimation of anxiety (100-point VAS). Results: Agreement between dentists' assessment of patients' anxiety and patient-reported anxiety proved good, intraclass correlation coefficient (177) = 0.63; 95% confidence interval [CI], 0.53-0.71. A small to medium-sized positive correlation, r (177) = 0.15; 95% CI, 0.00-0.29, was found between dentists' empathic accuracy and patient-reported reassurance. A negative correlation was found between empathic accuracy and patients' anxiety scores, r (177) = −0.23; 95% CI, −0.38 to −0.09. Conclusions: Given that greater empathic accuracy was associated with higher patient-reported reassurance during treatment, training young dental professionals in empathic accuracy might help patients feel reassured. Importantly, our results also suggest that with elevated levels of patient anxiety it is increasingly challenging for dentists to recognise this emotion, and thus support the patient in anoptimal manner.